Perceptions of Sustainable Marketing Management by Export Companies in Serbia - Čajka, Zoran I (Industrija, 2013)
The present research paper deals with perceptions of sustainable marketing management in the strategies of export companies in Serbia. The objectives in this paper are manifold. They are to emphasize the importance of green marketing management in export activities of domestic companies which pursue their green management plan; to evaluate the company’s share in specific marketing segments, and to highlight the significance of successful green marketing management in modern business. Domestic green-oriented companies, which export their products to many different countries, look into the possibility of increasing their sales volumes. The findings in the paper support the hypotheses that domestic companies are perceptive of sustainable marketing issues in their business activities, and sustainable marketing management is becoming an important factor in business activities of modern companies.
Keywords: Market segmentation; Perception; Marketing; Management; Export